A new family of zero-current-switching PWM converters and a novel HPF-ZCS-PWM boost rectifier - Wakabayashi, Fabio Toshiaki [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1999)
A new family of direct current (DC) to DC converters based on a zero current switching pulse width modulated (ZCS-PWM) soft commutation cell is presented. This ZCS-PWM cell is consists of two transistors, two diodes, two inductors and one capacitor; and provides zero voltage turn-on to the diodes, a zero-current turn-on and a zero-current zero-voltage turn-off to the transistors. In addition, a new commutation cell in a new ZCS-PWM boost rectifier is developed, obtaining a structure with power factor near the unity, high efficiency at wide load range and low total harmonic distortion in the input current.
Keywords: Electric commutation; Electric currents; Electric distortion; Electric power factor; Power converters; Pulse width modulation; Rectifying circuits; Resonant circuits; Zero current switching (ZCS) converters; Zero voltage switching (ZVS) converters; Power electronics